Transparent and flexible patient-specific aneurysm models for device testing (Transactions on Additive Manufacturing Meets Medicine, 2025)
Patient-specific intracranial aneurysm models play a pivotal role in the in vitro evaluation of endovascular devices. To enable robust testing and reflect physiological conditions, these models must be optically transparent, anatomically accurate, mechanically stable, and elastic. This study explores a multi-material, variable-thickness fabrication strategy using stereolithography 3D-printing (SLA) to optimize medical IA.IA models were constructed by [1]: a) segmenting vessels from medical radiological images (region growing, marching cube’s algorithms, MevisLab, MeVis Medical solution); b) manual correction of segmentation errors; c) addition of vessel wall and flow connectors; d) 3D printing (Form 3, Formlabs). A Clear V4 Resin (Material-1, Formlabs) was used to produce transparent models. The initial vessel wall was uniform with a thickness of 3 mm and offered sufficient structural durability. However, the optical visibility through the model was suboptimal. A modified design strategy was introduced, implementing a localized wall thickness reduction (?1 mm) at the aneurysmal sac while retaining thicker walls (3 mm) otherwise. This approach preserved model integrity during mechanical handling and connection to experimental circuits while enhancing visibility in regions critical for evaluating the efficiency of the endovascular devices.In addition, two elastomeric SLA materials (Formlabs), Elastic 50A (Material-2) and Flexible 80A (Material-3), at various wall thicknesses (1.0 mm, 0.8 mm, and 0.4 mm) were evaluated to mimic the biomechanical properties of human vasculature. Models produced with Material-2 were more transparent than Material-1 and -3  but failed to maintain form stability, especially at 0.4 mm. Material-3 improved tear resistance compared to Material-2 at 0.8 mm, albeit with reduced optical clarity. The investigation of Material-3 with 0.4 mm vessel wall thickness is ongoing.Wall thickness and material modifications can be used to balance transparency and mechanical performance. The proposed fabrication strategy supports the development of anatomically accurate, optically clear, and mechanically robust models for use in in vitro testing of endovascular devices.
Keywords: SLA; optical transparency; Additive Manufacturig; segmentation; cerebral aneurysm